Analisis Perlakuan Akuntansi Pada Restukturisasi Kredit Bermasalah Terhadap Non Performing Loan Di PT. BPR Dana Mandiri Bogor - Yuppy Triwidatin; Iin Sofiantari (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
NPL is one of the key clues to assess the bank’s abilities,as a result the high level of NPL is a strong hint of the bank failure to run a business asa result of problems inability topay a third party, debt can’t be billed, and reduced capital. The research aimed at figuring out just how effective a restructuring system can be for non performing loan. The method of data analysis used is qualitative data with a case study approach. In qualitative research data convergence is not directed by theory but directed by the evidence found at the time of researchin the field. Research shows that restructuring systems can help to weigh problem credits significantly at a time before restructuring in years 2020 in the amount of 2,35% an after a NPL restructuring in years 2021 in the amount of 2,17%.